Dementia caregiver burden association with community participation aspect of social capital - Papastavrou, Evridiki; Andreou, Panayiota; Middleton, Nicos; Tsangari, Haritini; Papacostas, Savvas S. (My University, 2015)
Abstract AIMS: This study explores dementia caregiver burden and depression in the context of social capital and investigates the relationship of caregivers' burden with the perceptions of social capital of a non-caregivers' group. BACKGROUND: Social capital is the range of social contact that gives access to social, emotional and practical support, but little is known about dementia patients and their care by the family in that context. DESIGN: A cross-sectional correlational study was undertaken. METHODS: Seventy family dementia caregivers matched to non-caregivers from the same neighbourhood participated in the study; three instruments were used to collect the data: the Zarit Burden Interview, the Centre for Epidemiological Studies-Depression scale and the Social Capital Questionnaire. Paired sample t-tests and correlation analysis were performed to examine all the hypotheses of interest. The data collection period was between October 2010-July 2011. RESULTS: Overall social capital scores were higher for the non-caregivers and lower for the caregivers with significant differences in each group. The correlation between caregiver burden and social capital showed that the overall burden score is significantly negatively related with the social capital factor 'non-caregivers' participation in the community'. CONCLUSION: Understanding the relation between caregiver burden and social capital will enhance nurses' capacity to explore the concept, the meaning and the politics of social capital to the benefit of dementia caregivers in the community.
Keywords: Dementia; Dementia caregivers; Nursing; Social capital; Social support